Changing the Endocrine Dependence of Breast Cancer: Data and Hypotheses - Nicolini, A.; Ferrari, P.; Biava, P.M.; Carpi, A. (Current Medicinal Chemistry, 2014)
Among the most common human cancers, often only breast and prostate cancers have advantage of hormone dependence. For a long time, this advantage permitted breast cancer to be efficaciously managed in the adjuvant and metastatic settings with low side effects by endocrine therapy. Unfortunately, soon or afterward hormone dependence is lost in most patients. In breast cancer, de novo or acquired hormone resistance is an hot issue and the focus of endless debate. Although a lack of oestrogen receptors (ERs) is considered to be the main reason for de novo hormone resistance, many studies have been conducted and many different mechanisms have been hypothesised to account for acquired hormone resistance. Thus far, hormone resistance appears to be occasionally delayed or avoided in “in vivo” experiments. However, this finding did not have a significant benefit in current clinical practice. The principal aim of this review article is to sum up and update the issue of changing the endocrine dependence of breast cancer. Recent molecular insights extensively elucidating and shedding new light on this very controversial issue are considered. Moreover, based on our recent reports, a new mechanistic interpretation of and a therapeutic approach for overcome hormone resistance are proposed.
Keywords: oestrogen receptor phosphorylation